(untitled) (Journal of actual problems of jurisprudence, 2015)
The article deals with the problems of integration of legal education in the world educational space. In connection with increasing requirements for specialists in the field of law in the modern world, the system of legal education should be reformed in several ways. Legal education in Kazakhstan should be adapted to implement the principles of the Bologna Declaration, such as academic mobility, the individualization of the educational process, the quality of education, and others. Key words: juridical education, training, credit technology, legal system.